2017
DOI: 10.1186/s40798-017-0107-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-term confinement and the efficacy of exercise countermeasures on muscle strength during a simulated mission to Mars: data from the Mars500 study

Abstract: BackgroundIsolation and long duration spaceflight are associated with musculoskeletal deconditioning. Mars500 was a unique, high-fidelity analogue of the psychological challenges of a 520-day manned mission to Mars. We aimed to explore the effect of musculoskeletal deconditioning on three outcome measures: (1) if lower limb muscle strength was reduced during the 520-day isolation; (2) if type I or II muscle fibres were differentially affected; and (3) whether any 70-day exercise interventions prevented any iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…A modest derangement of FPG was observed also in the 105-day simulated Mars mission [8], but in this situation coninement produced an FPG increase during the irst 5 weeks without indications of development of insulin resistance, probably because the observation time was too short to elicit such phenomenon in young healthy subjects. Interestingly, some contribution to insulin resistance may also derive from skeletal muscle changes, which have recently been described in the participants to the Mars-500 experiment [5]. Moreover, some degree of insulin resistance seems a common feature of conditions comparable to the 520-day isolation/coninement, such as, for example, people living in polar regions [7].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A modest derangement of FPG was observed also in the 105-day simulated Mars mission [8], but in this situation coninement produced an FPG increase during the irst 5 weeks without indications of development of insulin resistance, probably because the observation time was too short to elicit such phenomenon in young healthy subjects. Interestingly, some contribution to insulin resistance may also derive from skeletal muscle changes, which have recently been described in the participants to the Mars-500 experiment [5]. Moreover, some degree of insulin resistance seems a common feature of conditions comparable to the 520-day isolation/coninement, such as, for example, people living in polar regions [7].…”
Section: Discussionmentioning
confidence: 90%
“…This unique experiment provided an outstanding opportunity to evaluate the changes in psychological and physiological adaptation over 520 days of coninement [1], by simulating the crew's coninement, cohabitation and communication to Earth, along with the speciic activities and workload taking place in these conditions [2]. Previous reports on the Mars-500 project described mood and sleep-wake changes [3,4], as well as modiications of muscle strength [5] and autonomic nervous system function [6] and of some circulating biomarker levels associated with chronic environmental stress [3]. The potential body composition and metabolic changes associated with these psychological and physiological features have, however, not yet been reported.…”
Section: U N C O R R E C T E D P R O O F Introductionmentioning
confidence: 99%
“…Mission planning could also consider the possibility of short term fasting during periods of high solar activity at solar maximums. However, one must also consider the impact of such a strategy on other countermeasures such as physical exercise to prevent musculoskeletal and aerobic astronaut deconditioning (75). However, Winnard et al (76) recently showed that breaks in exercise of up to 7 days are unlikely to have a major impact on musculoskeletal deconditioning.…”
Section: Implications For Human Spaceflightmentioning
confidence: 99%
“…Physiological decline occurs despite participation in exercise countermeasures, which are a potent stimulus to promote musculoskeletal and cardiovascular adaptation (Trappe et al , 2009 ) and optimal immune function (Simpson et al , 2015 ) on Earth. While vestibular adaptations take place in the first days after transition to the microgravity environment, decline in musculoskeletal, cardiovascular, and immune systems can worsen with missions of greater duration (Fitts et al , 2010 ; Strollo et al , 2018 ), potentially limiting our capacity for interplanetary missions such as to Mars (Gaffney et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%